THE CURRENT RESEARCH TREND OF ISLAMIC EDUCATION IN INDONESIA PESANTREN AND ITS PROPERTIES - Ulum, Bahrul; Qosim , Nanang; Singh , Sanju_Kumar (Khulasah : Islamic Studies Journal, 2024)
Globalization disrupted the value of norms and religion in young generations. Islamic education in pesantren could become a medium to increase the awareness of people about the importance of Islamic principles in their lives. However, not many previous studies are well-known globally by overseas researchers and academicians. This study has the purpose of observing the development of research about Islamic education in pesantren in Indonesia. This paper used bibliometric analysis to collect and analyze the secondary data of previous studies from the Scopus website. There were 113 documents found in Scopus from 1994-2023. The data were analyzed using two software, Vosviewer and R Studio. The analysis was divided into 2, citation analysis and mostly used word analysis. The result showed that the most current words used as the author’s keywords were pesantren education, accommodation, management, effective schools, conservative, and developing countries. No word related to technology or digitalization was used either in the author’s keyword or abstract of previous studies that were reflected as the current situation of the 4th industrial revolution today. Moreover, the affiliation of the author with the highest number of citations was the UK. Indonesian authors were ranked 2nd, 3rd, 3rd, and 5th. There were also some authors whose affiliations were not countries with Muslims as the majority of the citizens.